Trending practices and discussions in contemporary English-language historiography of philosophy - Menzhulin, Vadym (Sententiae, 2022)
This article outlines the leading trends in contemporary English-language historiography of philosophy. It is shown that the anti-historicity, which was characteristic of analytic philosophy in its classical versions was only a moment in its development. A historical turn that began in English-language philosophical world as early as the 1960s, during the first decades of the 21st century has led to a true flourishing of the history of philosophy - both at the conceptual and institutional level. Contemporary English-speaking historians of philosophy pay considerable attention to the methodologically important distinction between real historical process, i.e., facts that took place in the past (history of philosophy), and reflections concerning means, goals, and epistemological foundations for the understanding of these facts (historiography of philosophy). It is also shown that one of the main results of a careful study of history of philosophy is inclusiveness – drawing attention to those pages or aspects of the past that, for some reason, were marginalized or completely forgotten. Factors that were traditionally dismissed as external and unimportant, now acquire the same significance as those that were previously considered as exclusively internal and important. Due to this fact traditional history of philosophy, focused primarily on the study of the most prominent representatives of Western thought, usually men by gender, is replaced by a much broader historically-philosophical canon, which includes a much wider circle of thinkers, representatives of different cultures and types of philosophizing.